2013
DOI: 10.1007/s11663-013-9844-6
|View full text |Cite
|
Sign up to set email alerts
|

Austenite Grain Growth and the Surface Quality of Continuously Cast Steel

Abstract: Austenite grain growth does not only play an important role in determining the mechanical properties of steel, but certain surface defects encountered in the continuous casting industry have also been attributed to the formation of large austenite grains. Earlier research has seen innovative experimentation, the development of metallographic techniques to determine austenite grain size and the building of mathematical models to simulate the conditions pertaining to austenite grain growth during the continuous … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 16 publications
0
12
0
1
Order By: Relevance
“…Different studies are available for continuous casting simulation in the Gleeble machines [2,3,[14][15][16]. Studies performed on this subject are generally related to the effect of strain rate, cooling rate, holding period before tensile test, austenite grain size and chemical composition on ductility.…”
Section: Open Accessmentioning
confidence: 99%
See 1 more Smart Citation
“…Different studies are available for continuous casting simulation in the Gleeble machines [2,3,[14][15][16]. Studies performed on this subject are generally related to the effect of strain rate, cooling rate, holding period before tensile test, austenite grain size and chemical composition on ductility.…”
Section: Open Accessmentioning
confidence: 99%
“…Transverse surface cracks seen on the continuous casting slabs have a great importance in the continuous casting process defects [1][2][3][4][5][6][7][8]. Crack-free slab production is an important key to success.…”
Section: Introductionmentioning
confidence: 99%
“…At this temperature exclusively b phase is present, in agreement with findings of Schwaighofer et al [9] The grain boundaries are clearly delineated as shown in the inset of Figure 2. [20] A square of about 2 mm side length, with a homogeneous temperature distribution, was mapped in preselected time intervals in order to gain statistically relevant data of grain size. a grain boundary groove that was formed at an earlier stage will remain visible as a groove even though grain growth had occurred and the new grain boundaries are located in different areas).…”
Section: Grain Growth In the Single B-phase Field Regionmentioning
confidence: 99%
“…When the initial austenite grain is infinitely small, the driving force will be infinite, which is not allowed in the mathematical model. The initial temperature of austenite transformation is set to 1,440 ℃ in the model [5] , and the initial austenite grain size is set to 100 μm, which is in the range of primary dendrite arm spacing.…”
Section: Austenite Growthmentioning
confidence: 99%
“…However, the hot ductility of micro-alloyed steels remains very poor during continuous casting, which leads to the formation of transverse cracks during the straightening process [3,4] . The influence factors of hot ductility in the third brittle zone include the size of austenite grain, carbonitride precipitation and pro-eutectoid ferrite film [5,6] . Research concerning the impact of Ti(C,N) precipitation on the growth of austenite mainly focuses on the hot Abstract: Austenite grain size is an important influence factor for ductility of steel at high temperatures during continuous casting.…”
mentioning
confidence: 99%